Prediction, prevention, and management of right ventricular failure after left ventricular assist device implantation: A comprehensive review - Rodenas-Alesina, Eduard; Brahmbhatt, Darshan H.; Rao, Vivek; Salvatori, Marcus; Billia, Filio (Frontiers in Cardiovascular Medicine, 2022)
Left ventricular assist devices (LVAD) are increasingly common across the heart failure population. Right ventricular failure (RVF) is a feared complication that can occur in the early postoperative phase or during the outpatient follow-up. Multiple tools are available to the clinician to carefully estimate the individual risk of developing RVF after LVAD implantation. This review will provide a comprehensive overview of available tools for RVF prognostication, including patient-specific and RV-specific echocardiographic and hemodynamic parameters, to provide guidance in patient selection during LVAD candidacy. We also offer a multidisciplinary approach to the management of early RVF, including indications and management of right ventricular assist devices in this setting to provide tools that help managing the failing RV.